The Current Questions of Police Speed Control - Major, Róbert; Mészáros, Gábor (Magyar Rendészet, 2016)
Traffic safety is one of the most important issues in Hungary and in the European Union. The authors survey the current state of affairs in Hungary in this respect. They examine the measures taken towards traffic safety and speed control in the past years in Hungary also analysing changes in the number of fatal accidents.